Evolution of Vehicles : Analyzing Security Vulnerabilities in Modern Automotive Technologies - Yashavi Singh; Akansha Shukla; Yusra Jameel; Dr. Kunal Gupta (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The evolution of vehicles has been a tribute to innovation of human ingenuity and brilliance. From simple carts to sophisticated electric and self-driving vehicles, evolutions of vehicles have been mirroring the technological advancements and cultural shifts of each era. The first vehicle was invented in the late 19th century, and ever since then the vehicles have been gracefully evolved. With the development of the vehicles their usage also increased many folds. From the means of daily transport, vehicles started symbolizing a status of luxury, and with this development came the usage of technologies that drives the features of a vehicle. Our paper explores and dwells into the security vulnerabilities related to the modern era vehicles, as the technology today can, on one hand ensure the novelties in the modern era and on the hand can prove to be an evil tool in the hands of notorious criminals.
Keywords: Security; Threats; Vulnerabilities; RFID; Multi-Factor Authentication